Pengembangan Nutrasetikal Es Krim Daun Kelor (Moringa oleifera L.) - Ul Haq, Takdir (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2022)
Moringa plants ranging from fruit, flowers, leaves, skin, seeds, stems to roots have important benefits. One of the most prominent content of moringa is antioxidants, especially in the leaves which contain high antioxidants. Moringa leaves contain antioxidants in the form of interquinones, flavonoids, tannins, steroids, alkaloids, triterpenoids, and saponins. Moringa leaves also contain vitamin C, calcium, B vitamins, iron, vitamin A, potassium and large amounts of protein that are easily digested and absorbed by the body. The use of moringa plants in Indonesia is currently still limited. One of the efforts to increase the utilization of moringa leaves is through the development of nutraceutical products of Moringa Leaf ice cream. This study aims to obtain a nutraceutical formulation of moringa leaf ice cream for and antioxidant activity. This research is an experimental study by conducting experiments to make Moringa Leaf powder by drying at room temperature and used as an additive in ice cream products and measuring antioxidant activity. This study shows that moringa leaf powder can be formulated into nutraceutical ice cream preparations, the antioxidant activity of moringa leaf powder 50 mg and 5% ice cream is classified as weak, moringa leaf powder 100 mg and 150 mg and 10% and 15% ice cream is classified as moderate and the antioxidant activity is moderate. Moringa leaf powder did not change after being formulated into a nutraceutical preparation of moringa leaf ice cream.